Mapping Publication of Gus Dur Thought: a Bibliometric Study - Pungki Purnomo; Dila Wahyuni (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2022)
Gus Dur is a well-known multidisciplinary Muslim intellectual figure. This study focuses on exploring the immortality of Gus Dur's thoughts which are available in different formats of publications written by himself or written by other authors. A bibliometric approach is used to analyze data in terms of the subject matter of the study, type of work, language, author's profession, and publisher. The population of this research is 635 works obtained from Google Scholar and Wahid Institute Library. Based on the Slovin formula, 86 sample works are taken. The study's results revealed that out of 86 works, there are 17 works written by Gus Dur and 69 by other authors. This study found 18 subjects of discussion. Nearly half of publications are in the format of books (25 works) almost all publications are written in Indonesian (76 works). Most of the writings about Gus Dur were written by lecturers (32 works). The works written by other people were almost entirely published after Gus Dur's death. Various formats of publications are identified; there are 13 books, 29 journals, 1 magazine, 23 theses (undergraduate) and 2 theses (S2). The study on the publication of Gus Dur can be used as a reference for people who want to investigate his life and thoughts.